Revitalizing the Role of Teachers in Islamic Education Learning Amidst Technological Developments - Mufid, Ahmad Imam; Sri Aminah; Moh. Ali Hafid (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study discusses the revitalization of the role of teachers in Islamic Education learning amidst rapid technological developments. Islamic Religious Education (PAI) teachers are faced with the challenge of adapting their traditional role as information transmitters to become facilitators and innovators of technology-based learning, without abandoning Islamic values. The purpose of this study is to formulate concrete strategies to strengthen the role of teachers so that PAI learning is more effective and contextual in the digital era. This study uses a descriptive qualitative approach through a literature review of scientific literature, educational policies, and related digital sources, with a study period spanning from 2015 to 2025. The results of the study indicate that there has been a shift in the role of PAI teachers from material transmitters to innovative learning facilitators, although technology integration is still limited to media adaptation without in-depth reinforcement of Islamic values. The main obstacles include low teacher digital literacy, limited infrastructure, and a learning paradigm that is still teacher-centered. The proposed revitalization strategy includes TPACK-based training, the development of a sharia-compliant LMS, the establishment of a digital PAI teacher professional learning community, and the implementation of blended-flipped Islamic values-based learning. Multi-stakeholder collaboration and affirmative government policies are needed to realize effective, contextual, and relevant Islamic Religious Education learning in the digital age